A multivariable miRNA signature delineates the systemic hemodynamic impact of arteriovenous shunt placement in a pilot study - Henn, Dominic; Abu-Halima, Masood; Kahraman, Mustafa; Falkner, Florian; Fischer, Katharina; Barrera, Janos A.; Chen, Kellen; Gurtner, Geoffrey C.; Keller, Andreas; Kneser, Ulrich; Meese, Eckart; Schmidt, Volker-Jürgen (Scientific reports, 2020)
Arteriovenous (AV) fistulas for hemodialysis can lead to cardiac volume loading and increased serum brain natriuretic peptide (BNP) levels. Whether short-term AV loop placement in patients undergoing microsurgery has an impact on cardiac biomarkers and circulating microRNAs (miRNAs), potentially indicating an increased hemodynamic risk, remains elusive. Fifteen patients underwent AV loop placement with delayed free flap anastomosis for microsurgical reconstructions of lower extremity soft-tissue defects. N-terminal pro-BNP (NT-proBNP), copeptin (CT-proAVP), and miRNA expression profiles were determined in the peripheral blood before and after AV loop placement. MiRNA expression in the blood was correlated with miRNA expression from AV loop vascular tissue. Serum NT-proBNP and copeptin levels exceeded the upper reference limit after AV loop placement, with an especially strong NT-proBNP increase in patients with preexistent cardiac diseases. A miRNA signature of 4 up-regulated (miR-3198, miR-3127-5p, miR-1305, miR-1288-3p) and 2 down-regulated miRNAs (miR30a-5p, miR-145-5p) which are related to cardiovascular physiology, showed a significant systemic deregulation in blood and venous tissue after AV loop placement. AV loop placement causes serum elevations of NT-proBNP, copeptin as well as specific circulating miRNAs, indicating a potentially increased hemodynamic risk for patients with cardiovascular comorbidities, if free flap anastomosis is delayed.
Gesehen am 02.04.2022